Проблема зайнятості сільського населення у неформальному секторі економіки - Решитько, Т. В.; Шинкаренко, А. В; Reshitko, Т.; Shinkarenko, А. (КНТУ, 2013)
Стаття присвячена розгляду питань зайнятості сільського населення у неформальному секторі економіки. Reformation of agrarian sector of economy, social and labour relations resulted in considerable changes in the structure of employment of rural population. The newly created private agricultural enterprises considerably decrease the number of the hired workers.Significant part rural population tends to act in different non-traditional forms of independent selfemployment without official registration. It resulted in appearance of new, unknown before, informal sector of economy in villages. Nearly every second village habitant is occupied in that sector. The informal sector of rural economy extends possibilities for the new types of economic activity, which did not exist before or were monopolized by the state. This sector provides services to economic segments that are avoided by the registered sector because of lower level flexibility and high cost of labour. The article discloses the issues of employment of rural population in the informal sector of economy and the ways of its legalization.
Problems of employment of rural population in the informal sector of economy
Keywords: неформальний сектор економіки; нерегламентована; „тіньова” зайнятість сільського населення; informal sector of economy; "shadow" employment of rural population unregulated